Logic Leads to Understanding = Knowledge - Schroeder, Paul (European Journal of Applied Sciences, 2025)
A baby life starts by their seeing and feeling. Later one learns about people in the family and the home. The learning gradually grows from the neighborhood and local areas, including schools. Learning expands more distant to regions, counties and states that define locations. With school, one’s knowledge extends to countries, people, history and the whole world. Knowledge grows by finding facts, by reading and experiencing. Learning about space is different, we aren’t there. Knowledge comes from theories. The overall view of space can be found to be incorrect and needs total change. In 1543 - Copernicus switched the center of orbits to travel around the sun instead of around earth. Today the current model of the universe is distorting knowledge about space and blocks our ability to understand the real universe.